The dynamics of long-term subletting: Evidence from apartment-seeking university students in Sweden - Theo Herold; Fredrik Kopsch (Helsinki Graduate School of Economics, 2023)
Due to stringent regulation on the Swedish primary rental market, many individuals turn to long-term sublets to satisfy their housing demand. A lack of accessible data has made study of this market difficult. Using a unique dataset, we exploit weekly temporal variation over multiple treatment windows to analyze rent levels around the start of the Swedish university semester. We uncover strong effects, with monthly rent increasing between 3.31 percent and 4.22 percent during the treatment period. The effects peak immediately after the university semester has started and are concentrated to the tails of the distribution of living space. The results are robust to a range of alternative specifications and sample sizes.
Keywords: D4; R1; R21; R31; 330; rental market; long-term subletting; subletting market; difference-in-differences; rent control